INTEGRATED ENGLISH PHONOLOGY CONTEXTUAL-BASED IN TEACHING SPEAKING FOR GENERAL PURPOSES AT ENGLISH PROGRAM OF JAMBI UNIVERSITY: Integrated English phonology - Duti Volya (Universitas Jambi, 2020)
This action research was aimed to describe on how was teaching speaking for general purpose by integrating English phonology contextual-based. This action research carried out by the lecturers through cyclical action in order to overcome teaching cases occurred in the classroom. This research was divided into two cycles. Each cycle consisted of four meetings. Each cycle used four phases. They were planning, action, observation and reflection. At the planning phase, the researchers made the research plan. At action phase, the researchers did teaching based on lesson plan that has been formulated. Furthermore, the work reflected to see the strengths and weaknesses as a reference for the next plan. The subject of the research was students of English program. The numbers of the subject of this research were twenty five students of English program. The data were obtained by doing observation and test. In observation, researchers looked at students’ attitude in speaking. Tests were conducted to determine the student's skill in speaking. Based on the data analysis, it’s found that the percentage level of students’ speaking performance increased from the first cycle to the second cycle, and students were motivated to be more active in speaking activity. In the first cycle, seven students were in the category of a very high level of understanding and very active, on the second cycle increased to 14 students are at a very high level of understanding and very high activity. This percentage of improvement increased 28% from the first cycle to the second cycle. Activeness of students in the learning process will lead to high interaction between students and lecturers or between students and colleagues. It could be concluded that the integrated English phonology contextual-based in speaking for general purpose can enhance student performance in speaking and the activeness in learning.